2017
DOI: 10.1364/boe.8.005075
|View full text |Cite
|
Sign up to set email alerts
|

Open-source do-it-yourself multi-color fluorescence smartphone microscopy

Abstract: Fluorescence microscopy is an important technique for cellular and microbiological investigations. Translating this technique onto a smartphone can enable particularly powerful applications such as on-site analysis, on-demand monitoring, and point-of-care diagnostics. Current fluorescence smartphone microscope setups require precise illumination and imaging alignment which altogether limit its broad adoption. We report a multi-color fluorescence smartphone microscope with a single contact lens-like add-on lens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 35 publications
0
58
0
1
Order By: Relevance
“…Various low-cost microscopy platforms using portable devices such as cell phone cameras have been recently developed for various applications. In mobile devices, different illumination strategies have been reported including on-axis epi-illumination 15,16 , off-axis inclined illumination 17 , butt-coupling 18 , and total internal reflection 19 . In order to avoid out-of-focus background with these illumination schemes, either the sample is compressed to a thickness of ~10 µm by mounting it between two glass slides 20 or physical properties of the sample such as plasmonic enhancement due to the presence of a metal surface 17 or total internal reflection due to the presence of a refractive index change are exploited 19 .…”
Section: Imager Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Various low-cost microscopy platforms using portable devices such as cell phone cameras have been recently developed for various applications. In mobile devices, different illumination strategies have been reported including on-axis epi-illumination 15,16 , off-axis inclined illumination 17 , butt-coupling 18 , and total internal reflection 19 . In order to avoid out-of-focus background with these illumination schemes, either the sample is compressed to a thickness of ~10 µm by mounting it between two glass slides 20 or physical properties of the sample such as plasmonic enhancement due to the presence of a metal surface 17 or total internal reflection due to the presence of a refractive index change are exploited 19 .…”
Section: Imager Designmentioning
confidence: 99%
“…In mobile devices, different illumination strategies have been reported including on-axis epi-illumination 15,16 , off-axis inclined illumination 17 , butt-coupling 18 , and total internal reflection 19 . In order to avoid out-of-focus background with these illumination schemes, either the sample is compressed to a thickness of ~10 µm by mounting it between two glass slides 20 or physical properties of the sample such as plasmonic enhancement due to the presence of a metal surface 17 or total internal reflection due to the presence of a refractive index change are exploited 19 . Yet, to reliably read microarrays, a suitable device also needs to provide a large (5-75 mm), uniform, undistorted field of view with high spatial resolution (~10 µm), and the sensor response across the field of view must be calibrated to ensure a linear response.…”
Section: Imager Designmentioning
confidence: 99%
See 1 more Smart Citation
“…JPEG/MPEG algorithms. Recording the unprocessed raw-data ("snap-mode") makes the use of cellphones even more attractive for science [17,19,[31][32][33].…”
Section: Cellphone Data Acquisitionmentioning
confidence: 99%
“…The development of smartphones in the past decade has precipitated an explosion in the quality of optics and electronics available at low cost to the consumer. The development of smartphone‐based microscopes, spectrographs and other laboratory‐grade instruments have been widely reported . In the field of helminth detection, Bogoch et al have demonstrated the use of smartphone microscopy to accurately detect infections by a trained user in the field with moderate sensitivities and specificities .…”
Section: Introductionmentioning
confidence: 99%